SUBJECTIVE EXPERIENCE AND OBJECTIVE MEASUREMENT: INTEGRATING NEWTON'S LAWS AND SMARTPHONE SENSORS IN PHYSICS LEARNING - Nurul Fitria; Ishafit; Okimustava; Fida Afifah; Sri Wahyuni; Ermelinda; Zellius Ragiliawan (RADJA PUBLIKA, 2025)
In today’s digital era, physics education demands more contextual and technology-integrated approaches to bridge abstract concepts with real-world experiences. This study aims to develop an innovative approach in physics learning by utilizing smartphone sensors to analyze the vertical motion dynamics of an elevator based on Newton’s Laws. The experiment was conducted in a five-story elevator at BRIDA Surakarta using the Phyphox application, which employs the smartphone’s built-in accelerometer and barometer. The modes